Przestrzenne zróżnicowanie poziomu życia w Polsce na podstawie wyników wielowymiarowej analizy porównawczej - Sompolska-Rzechuła, Agnieszka (Spatial Differentiation of the Level of Living in Poland on the Basis of Multidimensional Analysis Results, 2007)
The conception of the level of living quality is connected with the category of needs. In the period of systemic changes in Poland, investigation of these categories has got more meaning. The aim of the article is the presentation of results of comparative analysis of the level of living using chosen multidimensional methods. In the literature of the subject it is possible to find many definitions of the term "the level of living". In the analysis of this category many aspects of life are taken into account. They are: the food, conditions of residence, clothes, health protection, education, upbringing, personal safety, social environment (work conditions, sociopolitical activity, access to information), physical environment (the cleanness, public utilities, beauty of natural environment). The preliminary list of diagnostic variables characterizing studied phenomenon is numerous, the variables can be related to each other and can duplicate information about studied objects. The matrix of correlation coefficients was the basis of making a reduction of preliminary list of diagnostic variables with the use of a parametric method. The final set of features was set and used to analyse the level of living in provinces of Poland in 2004. The Principal Component Analysis (PCA) and chosen taxonomic methods (the linear arrangement analysis of aggregations) were used. The groups of provinces with similar level of living were set up.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 262-274